Investigation of Diarrheal Outbreak in a Cantonment: Implementation of Epidemiological Triad to Reach Diagnosis (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Acutediarrheal outbreak in Bangladesh prevails as an important cause of mortality and morbidity.In the month of April 2018, a diarrheal outbreak occurred in ‘Formation Recruit Training Center (FRTC)’ at ‘Jashore Cantonment’. A total number of 262 cases were detected.Objective: To find out the cause of outbreak.Materials and Methods:In three dimensional aspect investigation was done. Namely case detection and hypothesis generation, laboratory investigation and environmental investigation.Results:In 62% cases the sufferers were in the last half of second decade who were first exposed to the water of the Jsr cantonment. In stool culture no organism was found but mucus was seen in all (n=12) cases. In water bacteriological test water samples were highly contaminated with E coli and found unsatisfactory in 67% cases.Discussion:Administration of antibiotic prior to taking stool sample caused ‘false negative’ result in ‘antibiogram’.But the environmental investigation supported E coli mediated diarrhea outbreak strongly. Water was highly contaminated with bacteria. The host was immunologically sound due to stress. The agent was exposed for the first time.Conclusion: The environment in which they used to live was very poor. This ‘Epidemiological Triad’ of agent, hosts and environment caused them victim in a large scale.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 148-150